The role of surgery in managing recurrent hyperparathyroidism - Almottowa, Hisham Abdullah; Aldaihani, Manal Hussein; Alkandari, Ali Mohammad; Alghabban, Mohammad Mahroos; Aljabr, Abdullatif Hassan; Alotaibi, Monirah Khaled; Alduosari, Madhawi Fahad; Alamri, Abdulmajeed Muslih; Almogheer, Bader Hussain; Alrasheedi, Danah Mohammad (International Journal Of Community Medicine And Public Health, 2024)
Recurrent hyperparathyroidism (RHPT) presents a complex surgical challenge after initial treatment for primary hyperparathyroidism (PHPT). Characterized by hypercalcemia following a previously successful parathyroidectomy, RHPT requires accurate diagnosis and careful management to avoid complications. Preoperative imaging advancements and intraoperative parathyroid hormone (PTH) monitoring have reduced recurrence rates from 30% to 2.5%-5%, though they can be as high as 14% in some cases. Persistent hyperparathormonemia, multigland disease (MGD), and conditions such as parathyroid carcinoma contribute to recurrence. Factors such as age, imaging results, and PTH levels influence recurrence risk, with studies identifying older age and double adenomas as predictors. Surgical reintervention carries significant risks, including recurrent laryngeal nerve (RLN) palsy and permanent hypocalcemia. Monitoring biochemical markers over time, including calcium and PTH levels, remains essential. This review explores the causes of RHPT, surgical management strategies, and factors predicting recurrence, with a focus on individualized patient care and minimizing surgical risks. Successful management requires a balance between reoperation necessity and potential complications.